2020
DOI: 10.21203/rs.3.rs-23164/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lay perspectives on social distancing and other official recommendations and regulations in the time of COVID-19: a qualitative study of social media posts

Abstract: Background Coronavirus disease (COVID-19) caused by a new form of coronavirus (SARS-CoV-2) first appeared in China end of 2019 and quickly spread to all counties of the world. To slow down the spread of the virus and to limit the pressure on the health care systems, different regulations and recommendations have been implemented by authorities, comprising amongst others the closure of all entertainment venues and social distancing. These measures have received mixed reactions, particularly from young individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Easing restrictions at a slower rate, and setting out (and sticking to) clear plans with unambiguous, measurable targets that must be achieved before easing restrictions may help increase trust in the Government, decrease worry about easing restrictions and decrease community tension. 23…”
Section: Resultsmentioning
confidence: 99%
“…Easing restrictions at a slower rate, and setting out (and sticking to) clear plans with unambiguous, measurable targets that must be achieved before easing restrictions may help increase trust in the Government, decrease worry about easing restrictions and decrease community tension. 23…”
Section: Resultsmentioning
confidence: 99%
“…Aspects related to occupation and fear of unemployment are issues to be considered. Essential portions of the population that survive informal work find it difficult to adhere to distancing, as they need to supplement their income, although they are on a temporary income transfer program 3,8,15 . Furthermore, the informal work context limits the conditions for protecting workers, with greater exposure to risks and the need to maintain informal activity as a means of survival.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of information, government officials' credibility, and uncertainty about the virus also affect adherence. How public health authorities report on the importance of distancing can bring higher or lower confidence in the measure 8,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Virtual and in-office care provided by primary care clinicians is vital during disasters and pandemics to route people away from ED and hospital use while providing continuity of care and urgent, nonemergency care. 5,13,14 News media provision of concrete behavioral recommendations, as with instructional messaging, during pandemic times can increase perceived self-efficacy and improve behavioral intentions. 16 However, we found that safety and protection messages were often contradictory, which may undermine trust, an essential element of risk communication.…”
Section: Safetymentioning
confidence: 99%
“…Media sources have a potent influence on public opinion, policy, and practice through selective communication about certain aspects of a perceived reality that become salient in the thinking and views of the public. 4 During the pandemic, social media has been examined for lay perspectives and regulations, 5 and medical professional opinions and recommendations. 6 News media has received less attention but also contributes importantly to public perception.…”
Section: Introductionmentioning
confidence: 99%